Correlación entre diagnóstico ecográfico e histopatológico de poliposis vesicular en la Clínica Good Hope 2008-2014 - Contreras Castro, Emiliano (2016)
Objective: To determine the correlation between sonographic diagnosis and histopathological results of gallbladder polyposis and find the positive predictive value of ultrasound in the diagnosis of this pathology. Material and Methods: It is a non experimental, transversal, descriptive and correlational study with a sample composed of all patients operated with a diagnosis of gallbladder polyps in the Good Hope Clinic between the years 2008 and 2014. A total of 128 patients were observed. Histopathological and sonographic reports of these patients were reviewed and the statistical correlation of both studies was sought by the test of Spearman. Results: Reveals that 67,2% were females and 32,8% were males; the average age was 43,4 years; 74,2% presented polyps by histopathological examination, of which 94,7% were pseudopolyps, with 82 % cases of cholesterolpolyps, only 5,3% were true polyps (adenomas) and none of them were malignant. The positive predictive value of ultrasound in the diagnosis of gallbladder polyposis was 74,21%. According to the Spearman coefficient the correlation between the number of polyps by ultrasonography and histopathology was low, direct and significant (Rho = 0,189; p = 0,032). Conclusions: We conclude that there is a correlation between the ultrasound diagnosis and histopathological result of gallbladder polyps and ultrasound can be considered a reliable method for the diagnosis of gallbladder polyps.